2020
DOI: 10.1590/0034-7167-2020-0225
|View full text |Cite
|
Sign up to set email alerts
|

Nursing appeals on social media in times of coronavirus

Abstract: Objective: to know and analyze the nursing appeals on social media during the COVID-19 pandemic. Method: it is a documentary, qualitative, descriptive, and exploratory research with data collected in publications in two social media. Two hundred ninety-five publications of nursing professionals published on Twitter and Instagram between March 11 and 20, 2020 were submitted to content analysis using ATLAS.ti resources. Results: four thematic categories emerged: #stayathome, #whereismyPPE, #nowweareheroes, #no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 9 publications
1
54
1
17
Order By: Relevance
“…Tornou-se notável a valorização da equipe de enfermagem e sua atuação no combate a pandemia, em diversas redes sociais pode-se encontrar manifestações e também agradecimentos. Mas também, serviu para que os trabalhadores pudessem reivindicar seus direitos pelas mídias sociais, obtendo um grande alcance em massa e tornando uma manifestação virtual por menos horas trabalhadas e mais equipamentos de proteção disponíveis 25 .…”
Section: Discussionunclassified
“…Tornou-se notável a valorização da equipe de enfermagem e sua atuação no combate a pandemia, em diversas redes sociais pode-se encontrar manifestações e também agradecimentos. Mas também, serviu para que os trabalhadores pudessem reivindicar seus direitos pelas mídias sociais, obtendo um grande alcance em massa e tornando uma manifestação virtual por menos horas trabalhadas e mais equipamentos de proteção disponíveis 25 .…”
Section: Discussionunclassified
“…Our results even covered many of the topics identified in those studies with a specific interest. For example, in the nursing appeals-related study [28], the emerged thematic categories of #stayathome and #whereismyPPE were also identified through our analysis and overlapped with some topics in the solidarity and encouragement category. Another example, the study exploring why people ignore the orders of the authorities [30] revealed reasons such as information pollution on social media, the persistence of uncertainty about the rapidly spreading virus, the impact of the social environment on the individual, and fear of unemployment.…”
Section: Comparison With Prior Workmentioning
confidence: 91%
“…We searched MEDLINE via PubMed for evidence available by August 31, 2020, using combinations of the following terms: ("COVID-19" OR "lockdown") AND ("social media" OR "Twitter" OR "Weibo") AND ("topic model" OR "content analysis"). The search retrieved 9 relevant studies [26][27][28][29][30][31][32][33][34] among 20 published articles. We further identified 1 more relevant study [10] by screening bibliographies and "similar articles" suggested by PubMed.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
See 2 more Smart Citations